2011
DOI: 10.2307/41409966
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Model for Measuring Fit Between A Firm's Competitive Strategies and Information Systems Capabilities

Abstract: To compete in a highly dynamic marketplace, firms must frequently adapt and align their competitive strategies and information systems. The dominant literature on the strategic fit of a firm's information systems focuses primarily on high-level measures of the strategic fit of a firm's overall IS portfolio and the impact of fit on business performance. This paper addresses the need for a more fine-grained approach for assessing the specific areas of misfit between a firm's competitive strategies and IS capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 35 publications
1
63
0
Order By: Relevance
“…Not only do firms have to align IT capabilities with company strategies in order to achieve a better internal adjustment, but a firm's environment also needs to be included in order to prevent firms from wasting their scarce resources [53] and to develop an ability to adapt to the changing environment that refers to IT capabilities.…”
Section: Hypotheses 1 (H1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Not only do firms have to align IT capabilities with company strategies in order to achieve a better internal adjustment, but a firm's environment also needs to be included in order to prevent firms from wasting their scarce resources [53] and to develop an ability to adapt to the changing environment that refers to IT capabilities.…”
Section: Hypotheses 1 (H1)mentioning
confidence: 99%
“…Unfortunately, perceptions provide latent factors with measurement errors rather than direct and objective measures of capabilities. Another option could be to gather information using a qualitative approach: investigate in depth all the processes of the firm, compare more than one firm by analysing several cases, and draw a conclusion regarding how firms compete and behave (see, for example [53]). However, a proxy and not a real measure or description applicable to any firm could be used.…”
Section: The Latent Nominal Variable Capturing Firms' Heterogeneity:mentioning
confidence: 99%
“…Kappelman et al (2013) mentioned that many high-performance businesses would apply low-cost, innovative, or differential strategic orientation with Management Innovation, like different salary and welfare; on the contrary, low-performance companies presented weaker salary and Management Innovation. Aiming at the research on management practice and organizational performance in Taiwan, McLaren et al (2011) indicated that an organization would apply different strategies with human resource management practice. From above discussions, organizational Management Innovation correlates to organizational strategies, and management innovation would change with strategic orientation.…”
Section: Management Innovationmentioning
confidence: 99%
“…If something fits, it has the right size, shape, character and/or other feature(s). In academic research, the level of fit is typically searched through pairs of interests, such as task-technology fit [20], personorganization fit [34,26], person-group fit [56], organization-environment fit [18], user-computer fit [52] and/or through a firm's competitive strategies-IS capabilities fit [38]. In ITBV research, "alignment" and "fit" concepts have been conceptually so close that a few of studies have treated them as synonyms [36,25,27].…”
Section: Fit and Alignmentmentioning
confidence: 99%